KEMAMPUAN MEMAHAMI PADANAN KATA BAHASA INDONESIA DI KALANGAN MAHASISWA IKIP SILIWANGI BANDUNG - Yenti Sulistian; Setya Susilawati; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Globalization is often referred to as the era that has resulted from the entry of foreign cultural expression. The impact of globalization can affect life, including the language aspect. Facts show among young people including students who use more Indonesian language. Of course this should be wary if you do not want the Indonesian language "disappeared" from the earth of Indonesia. This study aims: 1) to know the ability of IKIP Siliwangi students understand the Indonesian word equivalents; 2) to know the frequency of students of IKIP Siliwangi Bandung using the equivalent of the Indonesian word. This research uses descriptive qualitative, research object is student of IKIP Siliwangi Bandung. The instrument used is a questionnaire. Data collection techniques use simple calculation techniques. From the results of data analysis obtained: 1) the ability of IKIP Siliwangi Bandung students know the equivalence of the Indonesian word a number of 78.15%, 2) the frequency of students IKIP Siliwangi Bandung using the equivalent of the Indonesian word amount of 11.3%.